Book Notes [11, Spring 1983] - Kealey, Linda; Fitting, Peter; Doucette, Laurel (Labour / Le Travail, 1983)
The article provides reviews of: Women's History Sources: A Guide to Archives and Manuscript Collections in the United States, 2 v., edited by Andrea Hinding / review by Linda Kealey -- Marxism and Culture: The CPUSA and Aesthetics in the 1930s, by Lawrence H. Schwartz / review by Peter Fitting -- A Bibliography of Canadian Folklore in English, compiled by Edith Fowke and Carole Henderson Carpenter / review by Laurel Doucette.